Redescription of Phrurolithus flavipes (Araneae: Phrurolithidae), with the first description of the male - Marusik, Yuri M.; Zonstein, Sergei L.; Omelko, Mikhail M. (Zootaxa, 2015)
Phrurolithus C.L. Koch, 1839, with 71 named species, is the largest genus of the family Phrurolithidae, which contains 188 species belonging to 14 genera (Platnick 2014). It has an almost exclusively Holarctic distribution: 34 species are known from the Palaearctic, 35 are known from the Nearctic and two species are known from Hispaniola. The genus is rather poorly studied and has never been the subject of wide-scale revision. Almost half of its species are known from a single sex: 23 from females and nine from males. Additionally, 45 species are known from the original description only, and one species has never been illustrated (Platnick 2014).